Kajian Semiotik Kumpulan Puisi Tersebab Aku Melayu Karya Taufik Ikram Jamil - Elmustian; Arkha, Meiranisah; Rumadi, Hadi (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2021)
Semiotics is a method of analysis that examines signs. This collection of poems Tersebab Aku Melayu by Taufik Ikram Jamil works contains many semiotic elements such as icons, indexes, and symbols. This study only focused on 14 poems from 59 poetry collections Tersebab Aku Melayu by Taufik Ikram Jamil. In this study, three problem formulas examine semiotics, namely what are the icons contained in a collection of poetry Tersebab Aku Melayu by Taufik Ikram Jamil, what are the indices contained in a collection of poetry Tersebab Aku Melayu by Taufik Ikram Jamil, and what are the symbols contained in a collection of poetry Tersebab Aku Melayu by Taufik Ikram Jamil. This study aims to describe the semiotic collection of poetry Tersebab Aku Melayu by Taufik Ikram Jamil. The benefit of this research is to increase the reader's understanding and knowledge about literature, especially on the semiotic study contained poetry Tersebab Aku Melayu by Taufik Ikram Jamil. The theory used in this research is semiotic studies which include aspects of icons, index aspects, and aspects of the symbol. The research data that the writer took in the form of words in the form of phrases, clauses, and sentences in the text contained in a collection of poetry books. The technique of collecting data in this research is a literature study. While the analysis technique used is reducing data, presenting the data and drawing the conclusion. The data of this study amounted to 314, consisting of 14 poems. Each character experienced their stages of existence of the religious stage. The details of 314 data are as follow, in the aspect of the icon found 1n 274 data, the index aspect was found in 12 data, and the aspect symbol was found in 28 data.